Seasonal variations in intracellular trace element content and physiological parameters in the lichen Evernia prunastri transplanted to an urban environment - Vannini, Andrea; Paoli, Luca; Nicolardi, Valentina; Di Lella, Luigi Antonello; Loppi, Stefano (Acta Botanica Croatica, 2017)
In this study we investigated the seasonal variations in the intracellular content of 14 trace elements (Al, As, Ba, Cd, Ce, Cr, Cu, Fe, Mn, Ni, Pb, Pd, Sb, Zn) and physiological parameters (namely chlorophyll a, chlorophyll b, ergosterol, photosynthetic efficiency, cell membrane integrity) in the thalli of the lichen Evernia prunastri (L.) Ach. exposed to an urban environment (Siena, central Italy). Lichen thalli were collected before each exposure period from an unpolluted area and transplanted to 16 sites; every 3 months the thalli were retrieved and replaced with new ones. Exposed-to-control ratios of trace elements revealed a marked intracellular accumulation of Cd in summer and autumn, and of Sb in autumn and spring, possibly as a result of vehicular traffic pollution. However, considering the low absolute concentrations of these elements, the intracellular fraction of depositions may hardly have caused an impairment of physiological parameters. As a matter of fact, indicators of photobiont vitality (content of chlorophylls a and b and photosynthetic efficiency) did not show any fluctuation across seasons, while changes in the indicators of mycobiont vitality (cell membrane damage and ergosterol content) overall did reflect some seasonal changes and/or lichen growth.